Legal Issues in Value Added Tax (VAT) and Income Tax Policies Regarding Types of Taxes and Their Legal Basis - Wahyudiantara, Kadek (Yayasan Baru Haji Samsudin, 2025)
Legal issues in the implementation of Value Added Tax (VAT) and Income Tax (PPh) policies in Indonesia have become an essential concern in realizing fairness and legal certainty within the national taxation system. VAT and PPh serve as the main instruments of fiscal policy and contribute significantly to state revenue, yet frequent regulatory changes and overlapping provisions have created uncertainty and inconsistency in their application. Through a normative legal approach, this study examines the legal foundations of VAT and PPh as regulated in Law No. 8 of 1983 and Law No. 7 of 1983, as amended by Law No. 7 of 2021 on the Harmonization of Tax Regulations (UU HPP). The analysis reveals that although the reform through UU HPP strengthens the legal framework and enhances administrative transparency, challenges persist in achieving tax justice, compliance, and effective enforcement. Strengthening digital tax administration, ensuring regulatory consistency, and promoting taxpayer awareness are necessary steps to establish a fair, transparent, and sustainable taxation system in accordance with the principles of justice and legal certainty as mandated by the 1945 Constitution of the Republic of Indonesia.